Antibiofilm and Anti-Quorum-Sensing Activities of Novel Pyrazole and Pyrazolo[1,5-a]pyrimidine Derivatives as Carbonic Anhydrase I and II Inhibitors: Design, Synthesis, Radiosterilization, and Molecular Docking Studies - Ahmed Ragab; Sawsan A. Fouad; Yousry A. Ammar; Dina S. Aboul-Magd; Moustafa S. Abusaif (MDPI AG, 2023)
Nowadays, searching for new anti-infective agents with diverse mechanisms of action has become necessary. In this study, 16 pyrazole and pyrazolo[1,5-a]pyrimidine derivatives were synthesized and assessed for their preliminary antibacterial and antibiofilm activities. All these derivatives were initially screened for their antibacterial activity against six clinically isolated multidrug resistance by agar well-diffusion and broth microdilution methods. The initial screening presented significant antibacterial activity with a bactericidal effect for five compounds, namely 3a, 5a, 6, 9a, and 10a, compared with Erythromycin and Amikacin. These five derivatives were further evaluated for their antibiofilm activity against both S. aureus and P. aeruginosa, which showed strong biofilm-forming activity at their MICs by >60%. The SEM analysis confirmed the biofilm disruption in the presence of these derivatives. Furthermore, anti-QS activity was observed for the five hybrids at their sub-MICs, as indicated by the visible halo zone. In addition, the presence of the most active derivatives reduces the violacein production by CV026, confirming that these compounds yielded anti-QS activity. Furthermore, these compounds showed strong inhibitory action against human carbonic anhydrase (hCA-I and hCA-II) isoforms with IC50 values ranging between 92.34 and 168.84 nM and between 73.2 and 161.22 nM, respectively. Finally, radiosterilization, ADMET, and a docking simulation were performed.